Rab28 is a TBC1D1/TBC1D4 substrate involved in GLUT4 trafficking. Issue 1 (20th December 2016) - Zhou, Zhou; Menzel, Franziska; Benninghoff, Tim; Chadt, Alexandra; Du, Chen; Holman, Geoffrey D.; Al‐Hasani, Hadi
Abstract : The Rab‐GTPase‐activating proteins (GAPs) TBC1D1 and TBC1D4 play important roles in the insulin‐stimulated translocation of the glucose transporter GLUT4 from intracellular vesicles to the plasma membrane in muscle cells and adipocytes. We identified Rab28 as a substrate for the GAP domains of both TBC1D1 and TBC1D4 in vitro . Rab28 is expressed in adipose cells and skeletal muscle, and its GTP‐binding state is acutely regulated by insulin. We found that in intact isolated mouse skeletal muscle, siRNA‐mediated knockdown of Rab28 decreases basal glucose uptake. Conversely, in primary rat adipose cells, overexpression of Rab28‐Q72L, a constitutively active mutant, increases basal cell surface levels of an epitope‐tagged HA‐GLUT4. Our results indicate that Rab28 is a novel GTPase involved in the intracellular retention of GLUT4 in insulin target cells. Abstract :